Outcomes of permanent pacemaker implantation following transcatheter aortic valve replacement. (25th November 2020) - Fauchier, L; Bodin, A; Bisson, A; Herbert, J; Lacour, T; Saint Etienne, C; Clerc, J.M; Quilliet, L; Semaan, K; Ivanes, F; Pierre, B; Deharo, P; et al.
Abstract: Background: Conduction abnormalities leading to permanent pacemaker (PPM) implantation are common complications following transcatheter aortic valve replacement (TAVR). Whether PPM implantation placement is associated with adverse outcomes is unclear. The purpose of this study was to evaluate the incidence, predictors, and clinical outcomes of PPI following TAVR. Methods: Based on the administrative hospital-discharge database, we collected information for all patients treated with TAVR between 2010 and 2019 in France. Results: A total of 49, 201 patients with aortic stenosis treated with transcatheter aortic valve replacement (TAVR) using the balloon-expandable (BE) Edwards SAPIEN valve or the self-expanding (SE) Medtronic CoreValve were found in the database. Among them, 10, 019 (20.4%) had prior PPM implantation, including 476 (4.8%) treated with cardiac resynchronization therapy (CRT). New PPM implantation was required within 30 days of TAVR in 11, 010 patients (22.4%), which varied among those receiving self-expanding valves (24.7%) versus balloon-expanding valves (20.9%). There were 349/10, 010 patients (3.1%) treated with cardiac resynchronization therapy (CRT) within 30 days following TAVR. In a multivariable analysis comprising 38 variables (including among others underlying conduction disorders, Euroscore 2, Charlson comorbidity index, frailty score and type of implanted valve), prior PPM implantation was associated with an increased risk of all-cause death (adjusted hazard ratio [HR]: 1.10 95% CI 1.04–1.16). New PPM implantation was associated with even higher risk of mortality (adjusted HR: 1.21 95% CI 1.15–1.28). By contrast, previous CRT was associated with a lower risk of death during follow-up (adjusted HR: 0.78 95% CI 0.63–0.96), while PPM with CRT within 30 days of TAVR was not associated with a different risk of death (adjusted HR: 1.00 95% CI 0.80–1.24). Prior PPM and new PPM implantation were also associated with an increased risk of rehospitalization for heart failure (adjusted HR: 1.26 95% CI 1.19–1.32 and 1.18 95% CI 1.12–1.24, respectively). Previous CRT was associated with a non-significant lower risk of rehospitalization for heart failure (adjusted HR: 0.92 95% CI 0.77–1.09). Conclusions: Both previous PPM and early PPM implantation following TAVR are commonly seen in patients treated with TAVR, and they are associated with a higher risk of death and rehospitalisation for heart failure when compared to patients with no PPM. The fact that CRT when implanted before TAVR was associated with a better survival may deserve consideration when elaborating future optimal approaches for management of conduction disturbances in patients treated with TAVR. Funding Acknowledgement: Type of funding source: None